Friends, Lovers, and the Big Terrible Thing : A Memoir - Perry, Matthew (Flatiron Books, 2022)
So begins the riveting story of acclaimed actor Matthew Perry, taking us along on his journey from childhood ambition to fame to addiction and recovery in the aftermath of a life-threatening health scare. Before the frequent hospital visits and stints in rehab, there was five-year-old Matthew, who travelled from Montreal to Los Angeles, shuffling between his separated parents; fourteen-year-old Matthew, who was a nationally ranked tennis star in Canada; twenty-four-year-old Matthew, who nabbed a coveted role as a lead cast member on the talked-about pilot then called Friends Like Us . . . and so much more.